The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/532043
|View full text |Cite
|
Sign up to set email alerts
|

Load Balanced Congestion Adaptive Routing for Mobile Ad Hoc Networks

Abstract: In mobile ad hoc networks the congestion is a major issue, which affects the overall performance of the networks. The load balancing in the network alongside the congestion is another major problem in mobile ad hoc network (MANET) routing due to difference in link cost of the route. Most of the existing routing protocols provide solutions to load balancing or congestion adaptivity separately. In this paper, a congestion adaptive routing along with load balancing, that is, load balanced congestion adaptive rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…[23], none of them has addressed the interoperable part of it. Hence, heterogeneous network without the inclusion of interoperability is not the purely heterogeneous network.…”
Section: A Less Applicability Of Existing Congestion Controlmentioning
confidence: 99%
“…[23], none of them has addressed the interoperable part of it. Hence, heterogeneous network without the inclusion of interoperability is not the purely heterogeneous network.…”
Section: A Less Applicability Of Existing Congestion Controlmentioning
confidence: 99%
“…The ETT values of the links are updated using broadcast probing as described by authors in [7] and [8]. In order to obtain the values of interfering traffic load, the procedure of Saigal et.al [4] has been adapted. The values of the neighboring traffic queues are updated in the locality table using two types of broadcast.…”
Section: Diversity-based Multipath Routing Metric (Dmrm)mentioning
confidence: 99%
“…The researchers [2] [9] have identified that designing efficient routing metrics and protocols exhibit a significant impact in improving the performance of such networks. In particular, the performance and dependability of wireless multihop communications extensively depends on the capability of these routing protocols to effectively distribute the load on selected paths, considering the current and dynamic network conditions [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Để nâng cao hiệu năng mạng, đã có nhiều công trình nghiên cứu trong thời gian gần đây tập trung vào các giao thức điều khiển truyền dữ liệu nhằm giảm xác suất nghẽn, giảm độ trễ truyền tải, nâng cao thông lƣợng mạng [3,4,5,6]. Để đánh giá hiệu năng mạng theo các giao thức điều khiển đƣợc đề xuất, chúng ta có thể sử dụng mô hình mô phỏng, mô hình giải tích toán học hoặc đo bằng thực nghiệm.…”
unclassified
“…Với phƣơng pháp mô phỏng, chúng ta có thể sử dụng các phần mềm mô phỏng đang đƣợc sử dụng phổ biến hiện nay nhƣ NS-2 [7], OMNeT++ [8] hoặc OPNET [9]. Các tác giả trong [3,4,5,6] đã sử dụng phƣơng pháp mô phỏng để đánh giá hiệu năng của các giao thức đƣợc đề xuất. Với phƣơng pháp sử dụng mô hình giải tích toán học, ta có thể sử dụng lý thuyết hàng đợi, lý thuyết xác suất thống kê và dựa trên các giả thiết về đặc tính lƣu lƣợng đầu vào để phân tích hệ thống.…”
unclassified